Graphene film for lithium metal negative electrode protection and preparation method thereof

By using graphene film in lithium-ion batteries, the poor battery cycle performance caused by uneven deposition and dissolution of lithium metal negative electrodes is solved, and the stable interface and efficient ion transmission of lithium metal negative electrodes are achieved, which improves the cycle stability of the battery and Security.

CN119240681APending Publication Date: 2025-01-03NORTHWESTERN POLYTECHNICAL UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411363712.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-28
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The lithium metal anode in lithium-ion batteries has poor battery circulation performance, reduced Coulomb efficiency and safety risks due to unstable solid/liquid interfaces and lithium dendrites. Graphene reacts with lithium ions as an anode material, causing battery capacity to attenuate.

Method used

Defectively free graphene films are prepared by mixing flake graphite with intercalation agent, hydrogen peroxide solution treatment and ultrasonic assisted peeling, and applied to the surface of lithium metal negative electrode to stabilize the interface and inhibit the Dentite growth.

Benefits of technology

The uniform deposition and dissolution of lithium metal negative electrode is achieved, the cycle stability and safety performance of the battery is improved, the growth and volume expansion of lithium dendrites are avoided, and the service life of the battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119240681A_ABST
    Figure CN119240681A_ABST
Patent Text Reader

Abstract

The invention discloses a graphene film for lithium metal negative electrode protection and a preparation method thereof, belongs to the technical field of lithium batteries, and solves the problem of poor battery cycle performance caused by non-uniform deposition and dissolution of a lithium metal negative electrode in the prior art. The graphene film is formed by stacking graphene sheets, the structure is complete and free of defects, the thickness ranges from 0.02 micron to 1 mm, and the surface loading capacity ranges from 0.1 mg / cm < 2 > to 5 mg / cm < 2 >. The graphene film provided by the invention is applied to the surface of a lithium metal negative electrode, does not react with metal lithium and is stable in chemical property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and more specifically to a graphene film for protecting a lithium metal negative electrode and a preparation method thereof. Background Art

[0002] Lithium-ion batteries play a major role in energy conversion and storage in new energy vehicles and commercial energy storage. As a negative electrode material, lithium metal has a theoretical capacity of up to 3860mAh / g, which is about 10 times that of graphite. Lithium metal negative electrodes are widely studied and applied due to their advantages such as high energy density and low electrochemical potential. In practical applications, due to its active chemical properties, lithium metal negative electrodes will undergo irreversible chemical reactions with electrolytes, and lithium metal and electrolytes will be consumed to form a solid electrolyte interface film (SEI film). The unstable solid / liquid interface makes the lithium plating uneven and has poor mechanical properties, which leads to uneven flux when lithium ions pass through the membrane and the generation of lithium dendrites. In addition, the membrane is prone to rupture because it cannot adapt to the volume change of the lithium metal negative electrode during charging and discharging, causing lithium metal to come into contact with the electrolyte again, forming a new irreversible reaction, which is repeated, resulting in a decrease in the coulombic efficiency of the battery, an increase in internal resistance, and even a short circuit, resulting in safety problems. The continuous consumption of electrolyte leads to a decrease in its coulombic efficiency and a deterioration in cycle stability. The uncontrollable growth of lithium dendrites may pierce the diaphragm, causing the battery to short-circuit, exacerbating safety issues such as explosion. The volume expansion during the charge and discharge process can cause particle damage and structural damage of the electrode material, or enhance the interaction with the electrolyte diaphragm, which in turn leads to battery performance degradation or failure. During the charge and discharge process, the common problems such as the instability of the solid electrolyte interface (SEI), lithium dendrite growth and volume expansion have serious negative effects, making the negative electrode protection of lithium-ion batteries receive more and more attention.

[0003] Graphene is a kind of carbon atoms connected by sp 2 Two-dimensional carbon nanomaterials that are hybridized and connected into a hexagonal honeycomb shape occupy an important position in the development prospects of lithium batteries due to their high electrical conductivity, high thermal conductivity, high specific surface area and excellent mechanical properties. At present, in the synthesis of positive electrode materials for lithium batteries, due to the poor electrical conductivity and low lithium ion mobility of common positive electrode materials for lithium batteries, the positive electrode materials are compounded with graphene to improve their electrical conductivity and thus improve their rate performance. However, in terms of the negative electrode, when graphene is directly used as the negative electrode material, its rate performance is also greatly affected due to the large number of oxygen-containing groups on its surface decomposing or reacting with lithium ions during the charging and discharging process, causing the battery capacity to decay. Summary of the invention

[0004] The present invention provides a graphene film for protecting a lithium metal negative electrode and a preparation method thereof, so as to solve the problem of poor battery cycle performance caused by uneven deposition and dissolution of the lithium metal negative electrode in the prior art.

[0005] In a first aspect, the present invention provides a graphene film, which is composed of stacked graphene sheets and has a defect-free structure; the surface loading of the graphene film is 0.1 to 5 mg / cm 2 .

[0006] As a possible implementation, the thickness is 0.02 μm to 1 mm.

[0007] In a second aspect, the present invention provides a method for preparing a graphene film according to any one of the first aspects, comprising the following steps: mixing flake graphite, intercalation agent A and intercalation agent B, performing intercalation reaction, and obtaining intercalation graphite; adding hydrogen peroxide solution to the intercalation graphite for interlayer reaction, washing, and obtaining expanded graphite; uniformly dispersing the expanded graphite in an N-methylpyrrolidone solution, performing ultrasonic treatment, and obtaining a graphene slurry; performing film-forming treatment on the graphene slurry, and drying, and obtaining the graphene film; wherein the intercalation agent A is a cation of Cr 6+ and Fe 3+ One or a combination of two of the electrolytes; the intercalant B is a concentrated acid solution.

[0008] As a possible implementation, the mass fraction of the hydrogen peroxide solution is 3% to 30%; and / or the cation is Cr 6+ The electrolyte is chromium trioxide; and / or the cation is Fe 3+ The electrolyte is ferric chloride; and / or the concentrated acid solution is any one of hydrochloric acid with a concentration of 12M and sulfuric acid with a concentration greater than 98wt%; and / or the mass ratio of the flake graphite, the intercalation agent A and the intercalation agent B is 1:5-20:5-30.

[0009] As a possible implementation method, the duration of the intercalation reaction is 0.1 to 24 hours; and / or, the duration of the interlayer reaction is 1 to 168 hours; and / or, the conditions of the ultrasonic treatment are: power 200 to 500 W, duration 0.5 to 4 hours; and / or, the film-forming treatment is vacuum filtration; and / or, the conditions of the drying treatment are: temperature 30 to 200° C., duration 0.5 to 50 hours.

[0010] In a third aspect, the present invention provides an application of a graphene film described in any one of the first aspects or a graphene film prepared by the preparation method described in any possible implementation of the second aspect in a lithium metal battery.

[0011] As a possible implementation, the graphene film is used as a component of a battery anode.

[0012] In a fourth aspect, the present invention provides a lithium metal battery, wherein the anode comprises a component: a graphene film as described in any one of the first aspects or a graphene film prepared by the preparation method as described in any possible implementation of the second aspect.

[0013] As a possible implementation, the anode further includes a component metal foil.

[0014] The graphene film provided by the present invention is non-oxidized, has few defects, high quality and good quality. The excellent mechanical properties of defect-free graphene contribute to the stability of the lithium metal interface. When applied to the surface of the lithium metal negative electrode, it does not react with metallic lithium and has stable chemical properties. It builds a good ion transmission channel for the uniform deposition and dissolution of the lithium metal negative electrode, assists the uniform deposition and dissolution of the metal, and inhibits the growth of dendrites and volume expansion on the surface of the negative electrode during the service of the battery, improving the Li + The solvation structure of lithium metal batteries can improve their service performance such as cycle stability.

[0015] The present invention provides a method for preparing a graphene film, wherein flake graphite and an intercalation agent are mixed and reacted to obtain intercalation graphite, the intercalation graphite is treated with a hydrogen peroxide solution to obtain expanded graphite, the obtained expanded graphite is uniformly dispersed in an N-methylpyrrolidone (NMP) solution, and a graphene slurry of a certain concentration is prepared using an ultrasonic assisted peeling method; the obtained graphene slurry is subjected to a film forming treatment, and then subjected to a drying treatment to obtain a defect-free graphene film. The preparation method of the present invention has a controllable and simple process flow and low cost; and the pressing treatment step is omitted, the preparation process is simplified, and the preparation process is more efficient.

[0016] The graphene film for lithium metal negative electrode protection provided by the present invention is composed of stacked graphene sheets, and the graphene sheets construct a large number of transmission channels for lithium metal cations to achieve high flux of metal ions, which is conducive to the uniform deposition and shedding of lithium metal cations, thereby inhibiting the generation of dendrites on the negative electrode surface and improving the battery cycle stability. The film layer has good mechanical properties and effectively alleviates the structural changes and collapse caused by frequent ion deintercalation, and has a large application space in the protection of metal battery negative electrodes. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0018] Figure 1 This is an optical photograph of the graphene film A provided in an embodiment of the present invention.

[0019] Figure 2 This is a SEM result of the graphene film A provided in an embodiment of the present invention.

[0020] Figure 3 SEM comparison diagram of the negative electrodes of the lithium symmetric battery A and the lithium symmetric battery A1 provided in the embodiments of the present invention, wherein (a) is the lithium symmetric battery A1, and (b) is the lithium symmetric battery A.

[0021] Figure 4 This is a graph showing the cycle stability test results of the lithium symmetrical battery A provided in an embodiment of the present invention.

[0022] Figure 5 This is a graph showing the cycle stability test results of the lithium symmetrical battery B provided in an embodiment of the present invention.

[0023] Figure 6 This is a graph showing the cycle stability test results of the lithium symmetrical battery C provided in an embodiment of the present invention.

[0024] Figure 7 This is a graph showing the cycle stability test results of the lithium symmetric battery D provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] In order to solve the problem of poor battery cycle performance caused by uneven deposition and dissolution of lithium metal negative electrodes in the prior art, an embodiment of the present invention provides a preparation experiment of a graphene film.

[0027] Flake graphite and an intercalation agent are mixed and reacted to obtain intercalation graphite, the intercalation graphite is treated with a hydrogen peroxide solution to obtain expanded graphite, the expanded graphite obtained is uniformly dispersed in an N-methylpyrrolidone (NMP) solution, and a graphene slurry of a certain concentration is prepared using an ultrasonic assisted exfoliation method; the obtained graphene slurry is subjected to a film-forming treatment, and then subjected to a drying treatment to obtain a defect-free graphene film. The preparation method of the present invention has a controllable and simple process flow and low cost.

[0028] Furthermore, the SEM analysis of the prepared graphene film in the embodiment of the present invention shows that the film is smooth and flat, which is conducive to uniform ion transmission, and the excellent mechanical properties of the defect-free graphene contribute to the stability of the lithium metal interface.

[0029] Furthermore, the embodiment of the present invention carried out a performance verification experiment on the prepared graphene film, and it can be seen that the graphene film provided by the present invention is applied to the surface of the lithium metal negative electrode, does not react with metallic lithium, has stable chemical properties, and has better cycle stability.

[0030] The technical solution of the present invention will be further described below in conjunction with specific embodiments.

[0031] Example 1

[0032] This embodiment provides a preparation experiment of a graphene film.

[0033] 5g of flake graphite, 80g of chromium trioxide and 50mL of 12M hydrochloric acid were mixed, stirred for 2h, washed and filtered, and dried in a 60°C forced air drying oven for 10h to obtain intercalated graphite A. 400mL of hydrogen peroxide solution was added to the obtained intercalated graphite A for interlayer liquid phase reaction for 3d and then washed several times to obtain expanded graphite A; expanded graphite A was uniformly dispersed in N-methylpyrrolidone (NMP) solution and graphene slurry A was prepared using an ultrasonic assisted exfoliation method; it was filtered and filmed on Celgard 2325, and vacuum dried and heat treated at 150°C for 2h to obtain graphene film A, whose optical photograph is shown in the figure. Figure 1 shown.

[0034] The graphene film A was analyzed by SEM, and the following results were obtained: Figure 2 The results shown by Figure 2 It can be seen that the surface of graphene film A is smooth and flat, which is conducive to uniform ion transmission.

[0035] Example 2

[0036] This embodiment provides a preparation experiment of a graphene film.

[0037] 5 g of flake graphite, 80 g of chromium trioxide and 50 mL of 12M hydrochloric acid were mixed, stirred for 2 h, washed and filtered, and dried in a 60°C forced air drying oven for 10 h to obtain intercalated graphite B. 400 mL of hydrogen peroxide solution was added to the obtained intercalated graphite B for 3 days of interlayer liquid phase reaction and then washed several times to obtain expanded graphite B; it was filtered and filmed on Celgard 2325, pressed at a force of 5 kPa for 2 h, and vacuum dried and heat treated at 150°C for 2 h to obtain graphene film B.

[0038] Example 3

[0039] This embodiment provides a preparation experiment of a graphene film.

[0040] 5g of flake graphite, 80g of chromium trioxide and 50mL of 12M hydrochloric acid were mixed, stirred for 2h, washed and filtered, and dried in a 60°C forced air drying oven for 10h to obtain intercalated graphite C. 400mL of hydrogen peroxide solution was added to the obtained intercalated graphite C for interlayer liquid phase reaction for 3d and then washed several times to obtain expanded graphite C; expanded graphite C was uniformly dispersed in NMP solution to prepare graphene slurry C, which was filtered and filmed on Celgard 2325, pressed at a force of 5kPa for 2h, and vacuum dried and heat treated at 150°C for 2h to obtain graphene film C.

[0041] Example 4

[0042] This embodiment provides a preparation experiment of a graphene film.

[0043] 5g of artificial graphite, 80g of chromium trioxide and 50mL of 12M hydrochloric acid were mixed, stirred for 2h, washed and filtered, and dried in a 60°C forced air drying oven for 10h to obtain intercalated graphite D. 400mL of hydrogen peroxide solution was added to the obtained intercalated graphite D for 3d of interlayer liquid phase reaction and then washed several times to obtain expanded graphite D; expanded graphite D was uniformly dispersed in an aqueous solution and a graphene slurry D was prepared using an ultrasonic assisted exfoliation method; it was filtered and filmed on a Nylon membrane, pressed at a force of 5kPa for 2h, and vacuum dried and heat treated at 150°C for 2h to obtain a graphene film D.

[0044] Experimental Example 1

[0045] This experimental example provides an application performance test experiment of graphene film.

[0046] Assemble a lithium symmetric battery, use the negative electrode protective agent to be tested and the lithium metal foil as the metal battery anode, and assemble them together with the positive and negative electrode shells to obtain a lithium symmetric battery.

[0047] In this experimental example, the graphene films A to D prepared in Examples 1 to 4 were used as negative electrode protective agents to be tested, respectively, to assemble lithium symmetric batteries A to D, and a control group without the negative electrode protective agent to be tested was set up, namely lithium symmetric battery A1. The cycle stability was tested under the conditions of 2 mA current and 1 mAh deposition capacity. Figures 4 to 7 The results shown by Figures 4 to 7 It can be seen that the cycle time of lithium symmetric battery A reaches 200h; the cycle time of lithium symmetric battery B, lithium symmetric battery C and lithium symmetric battery D is 80h. It can be seen that the batteries with graphene film A as the negative electrode protective agent have good cycle stability.

[0048] The negative electrodes of lithium symmetric battery A and lithium symmetric battery A1 were analyzed by SEM, and the following results were obtained: Figure 3 The results shown by Figure 3It can be seen that graphene film A can effectively promote the uniform deposition of metal cations on the negative electrode surface and inhibit the growth of dendrites.

[0049] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0050] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A graphene film, characterized in that: The graphene film is stacked with graphene sheets and has no structural defects; the surface loading of the graphene film is 0.1-5 mg / cm 2 .

2. The graphene film according to claim 1, characterized in that: The thickness is 0.02μm~1mm.

3. A method for preparing a graphene film according to any one of claims 1 to 2, characterized in that: The following steps are involved: The flake graphite, intercalation agent A and intercalation agent B are mixed to perform an intercalation reaction to obtain intercalation graphite; Adding hydrogen peroxide solution to the intercalated graphite to carry out interlayer reaction, and washing to obtain expanded graphite; The expanded graphite is uniformly dispersed in an N-methylpyrrolidone solution and subjected to ultrasonic treatment to obtain a graphene slurry; Performing a drying process on the graphene slurry after film-forming process to obtain the graphene film; Wherein, the intercalant A is a cation of Cr 6+ and Fe 3+ One or a combination of two of the electrolytes; the intercalant B is a concentrated acid solution.

4. The preparation method according to claim 3, characterized in that: The mass fraction of the hydrogen peroxide solution is 3% to 30%; And / or, the cation is Cr 6+ The electrolyte is chromium trioxide; And / or, the cation is Fe 3+ The electrolyte is ferric chloride; And / or, the concentrated acid solution is any one of hydrochloric acid with a concentration of 12M and sulfuric acid with a concentration greater than 98wt%; And / or, the mass ratio of the flake graphite, the intercalation agent A and the intercalation agent B is 1:5-20:5-30.

5. The preparation method according to claim 3, characterized in that: The intercalation reaction time is 0.1 to 24 hours; And / or, the duration of the interlayer reaction is 1 to 168 hours; And / or, the conditions of the ultrasonic treatment are: power 200-500W, duration 0.5-4h; And / or, the film-forming process is vacuum filtration; And / or, the drying treatment conditions are: temperature 30-200° C., time 0.5-50 h.

6. Use of the graphene film according to any one of claims 1 to 2 or the graphene film prepared by the preparation method according to any one of claims 3 to 5 in lithium metal batteries.

7. The use according to claim 6, characterized in that: The graphene film is used as a component of a battery anode.

8. A lithium metal battery, characterized in that: The anode comprises components: the graphene film according to any one of claims 1 to 2 or the graphene film prepared by the preparation method according to any one of claims 3 to 5.

9. The lithium metal battery according to claim 8, characterized in that The anode also includes a component metal foil.

Citation Information

Patent Citations

  • Preparation method of fewer-layer graphene

    CN102583351A

  • Preparation method for graphene thin film current collector

    CN103903875A

  • Method for electrochemically preparing graphene

    CN105948025A

  • Graphene film for metal negative electrode protection and preparation method thereof

    CN117401672A

  • Method for preparing graphene dispersion and article thereof

    WO2017128929A1